The effects of whey vs. pea protein on physical adaptations following 8-weeks of high-intensity functional training (HIFT): A pilot study - Banaszek, A.; Townsend, J. R.; Bender, D.; Vantrease, W. C.; Marshall, A. C.; Johnson, K. D. (Sports, 2019)
This study examined the effects of whey and pea protein supplementation on physiological adaptations following 8-weeks of high-intensity functional training (HIFT). Fifteen HIFT men (n = 8; 38.6 ± 12.7 y, 1.8 ± 0.1 m, 87.7 ± 15.8 kg) and women (n = 7; 38.9 ± 10.9 y, 1.7 ± 0.10 m, 73.3 ± 10.5 kg) participated in this study. Participants completed an 8-week HIFT program consisting of 4 training sessions per week. Participants consumed 24 g of either whey (n = 8) or pea (n = 7) protein before and after exercise on training days, and in-between meals on non-training days. Before and after training, participants underwent ultrasonography muscle thickness measurement, bioelectrical impedance analysis (BIA), two benchmark WODs (workout of the day), 1-Repetition Maximum (1RM) squat and deadlift testing, and Isometric Mid-thigh Pull (IMTP) performance. Separate analyses of covariance (ANCOVA) were performed on all measures collected at POST. Both groups experienced increased strength for 1RM back squat (p = 0.006) and deadlift (p = 0.008). No training effect (p > 0.05) was found for body composition, muscle thickness, IMTP peak force, IMTP rate of force development, or performance in either WOD. Using PRE values as the covariate, there were no group differences for any measured variable. We conclude that ingestion of whey and pea protein produce similar outcomes in measurements of body composition, muscle thickness, force production, WOD performance and strength following 8-weeks of HIFT.